2022
DOI: 10.29228/jrp.114
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids and antioxidant capacities of three Centaurea L. species

Abstract: The aim of this study is to determine the fatty acid compositions and antioxidant activities of three Centaurea species as Centaurea iberica, C. urvillei ssp. hayekiana, and C. urvillei ssp. nimrodis and compare them with each other. As a result of fatty acid determination by GC MS method, oleic acid and linoleic acid were found as the main fatty acids in these Centaurea species. Polyunsaturated fatty acids (PUFAs) were determined at 58.66%, 46.98%, 62.22% in C. iberica, C. urvillei ssp. hayekiana and C. urvil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In a study by Gülçin et al, (2020) ABTS radical scavenging IC 50 values of Mentha pulegium were found as 7.92 µg mL -1 for methanolic extract and 9.37 µg mL -1 for aqueous extract. In a study by Taştan et al, (2022) ABTS radical scavenging IC 50 values for three different Centaurea species were found as 50.13, 98.43 and 75.04 μg mL -1 for methanolic extract. In a study by Ouissem et al, (2018) ABTS radical scavenging IC 50 values for Lepidium draba was found 39.42 μg mL -1 for ethyl acetate extract.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In a study by Gülçin et al, (2020) ABTS radical scavenging IC 50 values of Mentha pulegium were found as 7.92 µg mL -1 for methanolic extract and 9.37 µg mL -1 for aqueous extract. In a study by Taştan et al, (2022) ABTS radical scavenging IC 50 values for three different Centaurea species were found as 50.13, 98.43 and 75.04 μg mL -1 for methanolic extract. In a study by Ouissem et al, (2018) ABTS radical scavenging IC 50 values for Lepidium draba was found 39.42 μg mL -1 for ethyl acetate extract.…”
Section: Resultsmentioning
confidence: 96%
“…(Elazıg, Türkiye). The total phenolic substance amounts in the methanol extract of Centaurea species are 182 460, 40 2080 and 24 3910 μg GAE g -1 dry matter respectively (Taştan et al, 2022). In the study conducted by Alper et al, they found the total amount of phenolic substance in the ethanolic extract of Centaurea solstitialis as 52 310 μg GAE g -1 extract (Alper et al, 2021).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation